Process safety education of future employee 4.0 in Industry 4.0. (February 2022) - Gajek, Agnieszka; Fabiano, Bruno; Laurent, André; Jensen, Niels
Abstract: The term "Industry 4.0″, which refers to a fourth industrial revolution, is a recent neologism. The rise of digital technology including, artificial intelligence, the Internet of things and networks, "smart" and responsive devices, etc … is more and more omnipresent. In solving the related challenges of Industry 4.0, it is necessary to improve the involvement and training of employers and employees. This is particularly true for their education in process safety. Two surveys were submitted to the relevant stakeholders. Their results showed absence of Industry 4.0 topics in the current courses on process safety. On the other hand, a review of the master's degree programs available in Europe revealed the recent emergence of new highly specialized courses in some of the topics of Industry 4.0. The definition of "Safety 4.0″ leads to recommend two potential global training pathways, with one corresponding to the requirements of Industry 4.0 & Safety 4.0 intersections, recommended within the framework of pedagogical taxonomy models. Highlights: Employee 4.0 is a person that has adapted to a digitalized working environment. Adapt process safety learning to the digital transformation of Industry 4.0 It is time to develop Safety 4.0 offerings for skills developments. Education should prepare the training of future professionals for safety 4.0 Enhancing safety 4.0 education, a challenge of foresight for industry 4.0